2006
DOI: 10.1007/s11060-006-9126-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of matrix degrading enzymes and invasion in human glioblastoma (U87MG) Cells by isoflavones

Abstract: Glioblastoma multiforme is a primary brain tumor associated with extensive invasion into surrounding brain tissue. Matrix metalloproteinases (MMPs) and urokinase plasminogen activation (uPA) system are shown to be involved in tumor invasion as they help in degradation of extracellular matrix (ECM) proteins and thus assist in the movement of cells. MMP-2 and 9 were shown to be upregulated in gliomas, suggesting their involvement in invasion. Genistein and biochanin A are isoflavones commonly known as phytoestro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
69
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(75 citation statements)
references
References 41 publications
3
69
0
1
Order By: Relevance
“…37,38 Both LNPs had a tenfold higher uptake than PE-PEG-LNP ( Figure 5A), which was three times higher than observed for A/Chol-PCL-LNP ( Figure 4A). While it was observed that the LNPs with cholesterol-anchored PCL had an additive effect of dual-modification with both angiopep and PCL, this was not the case for DM-PCL-LNPs.…”
mentioning
confidence: 78%
“…37,38 Both LNPs had a tenfold higher uptake than PE-PEG-LNP ( Figure 5A), which was three times higher than observed for A/Chol-PCL-LNP ( Figure 4A). While it was observed that the LNPs with cholesterol-anchored PCL had an additive effect of dual-modification with both angiopep and PCL, this was not the case for DM-PCL-LNPs.…”
mentioning
confidence: 78%
“…This system can also activate cell proliferation pathways by interacting with other proteins like vitronectin and integrins (Sidenius & Blasi, 2003).Many studies and clinical trials are now focusing on anti-invasive chemotherapies as a treatment option for glibolastoma. Apart from synthetic derivatives, natural compounds in soy, curcumin can also inhibit glioblastoma invasion in vitro (Puli et al, 2006;Senft et al, 2010). Their activity in vivo warrants further research.…”
Section: Invasionmentioning
confidence: 99%
“…Biochanin A also inhibits the incidence and growth of xenograft tumors in athymic mice subsequent to injection of prostate cancer cells (LNCap) into the mice (Rice et al, 2002). We have demonstrated that both genistein and biochanin A inhibit invasion of glioblastoma cells by lowering the expression and activity of matrix-degrading enzymes (Puli et al, 2006). Soy isoflavones appear to be safe and effective in pre-clinical studies but clinical trials supporting their efficacy are still required (Virk-Baker et al, 2010).…”
Section: Isoflavonesmentioning
confidence: 99%
“…Several researchers have demonstrated that a variety of proteolytic enzymes, such as serine proteases and metalloproteinases, play crucial roles in tumor invasion and metastasis in several types of cancers (1)(2)(3)(4)(5)(6). The serine protease urokinase plasminogen activator (uPA) and its high affinity receptor, urokinase plasminogen activator receptor (uPAR), are responsible for extracellular degradation and cellular migration during various conditions such as inflammatory responses or tumor invasion (3).…”
Section: Introductionmentioning
confidence: 99%
“…The serine protease urokinase plasminogen activator (uPA) and its high affinity receptor, urokinase plasminogen activator receptor (uPAR), are responsible for extracellular degradation and cellular migration during various conditions such as inflammatory responses or tumor invasion (3). Furthermore, the uPA-uPAR system brings about several intracellular and intercellular processes including cleavage and activation of plasminogen to plasmin, remodeling of extracellular matrix (ECM), activation of growth factors, and initiation of intracellular signaling in response to various stimuli (7).…”
Section: Introductionmentioning
confidence: 99%